Lived Islam. An Empirical Study of the DITIB Mosque Communities in Germany (KULT_online, 2017)
In contrast to the majority of recent works that have tended to analyze Islam as a field of conflict and part of integration debates, the book Gelebter Islam: Eine empirische Studie zu DITIB-Moscheegemeinden in Deutschland by Theresa Beilschmidt focuses on the religious life and religious practices of DITIB mosque community members in Germany. It is based on the in-depth study of three mosque communities and ethnographic (participant) observations in the federal state of Hessen and presents an alternative look at Islam “from below”. By analyzing the empirical material, the author provides valuable perspectives on the main aspects of Muslim religiosity in the German society.